Vibration frequency, decoherence time and quality factors of phase rotation of qubit sphere by confined spherical Gaussian potential under electromagnetic field - Su, Du; Xin, Wei; Chelimuge; Li, Hong-Min (European physical journal plus, 2022)
In this paper, the theoretical conception of realizing qubit by using the spherical Gaussian confining potential donor center quantum dot (QD) is proposed, and the rationality and superiority of this conception are expounded. The wave functions and energies of the ground state and the first excited state of the system were calculated by using Pekar-type variational method, and then a qubit sphere was constructed. The decoherence of qubit induced by longitudinal optical (LO) phonon effect is studied by Lee-Low-Pines unitary transformation method in the case of strong electron-LO phonon coupling. The vibration frequency of qubit sphere is studied for the first time, and the mechanism that the quality factor of phase rotation of qubit spheres is actually the decoherence time regulated by the vibration frequency of qubit spheres is clarified. The effects of the intrinsic properties of materials such as dielectric constant ratio, dispersion coefficient and electron–phonon coupling constant as well as the doping and applied electromagnetic fields on the vibration frequency, decoherence time and phase rotation quality factors are revealed. Some interesting phenomena are found, such as: When the QD radius is about 4.0 r p , the decoherence time changes from increasing to decreasing with the increase in magnetic induction intensity. This phenomenon shows the good properties of magnetic field in suppressing decoherence; one property of the material often has different or even opposite effects on the different properties of the qubit. For example, increasing the dielectric constant ratio of the medium is not only conducive to the suppression of decoherence, but also conducive to the phase rotation control of the qubit sphere, but not conducive to the storage of the QD carrier qubit; moreover, the application of electric field is not conducive to the suppression of decoherence, nor is it conducive to the phase rotation control of the qubit sphere, but is conducive to the storage of the QD carrier qubit, etc. Based on these results, we have clarified in the inherent nature of the material, such as the dielectric constant ratio, dispersion coefficient and electron-LO phonon coupling constant, as well as the environment in the electromagnetic field, which is good for improve QD quantum information storage carrier, which is good for inhibiting qubit coherent elimination, which is good for improving qubit sphere phase rotation manipulation, etc. These can provide a theoretical basis for the technical scheme of adjusting the different properties of qubit spheres, such as information storage, decoherence and phase rotation control, by using the parameters of the material and the strength of electromagnetic field.